How to Correct Frontal Facialis Palsy After Radical Tumour Surgery: Upper Blepharoplasty and Direct Brow Lift - Wollina, Uwe (Medknow Publications & Media Pvt Ltd, 2011)
Radical surgery of fronto-temporal non-melanoma skin cancer (NMSC) sometimes causes palsy of the frontal facialis branch. Patients may experience visual impairment due to brow and upper eyelid ptosis. Since NMSC predominantly affects elderly people, the corrective surgical procedures have to be adapted to age, comorbidities and individual needs. The direct brow lift and the upper lid blepharoplasty are two reliable and safe surgical techniques with proved efficacy. Here we present our way to deal with post-surgical brow and lid ptosis.